Township-level governance in disaster preparedness in Yangon, Myanmar, during the period of transformation from April 2011 to January 2021 - Zin Mar Than; Hlaing Maw Oo; Sophie-Bo Heinkel; Toe Aung; Tin Tin Kyi; Saw Sandar Oo; Win Lei Mar; Win Maung; Zin Nwe Myint; Khin Khin Soe; Marlene Willkomm; Christian Miller; et al. (Natural Hazards, 2026)
Since Cyclone Nargis hit the country in 2008, Myanmar has stepped up its efforts to implement a disaster management system aimed at reducing disaster risk. At the same time, a far-reaching political and social transformation took place, shifting from military to civilian administration between April 2011 and January 2021. During this period, new concepts for disaster risk management were developed internationally, focusing on local governance and community-based strategies. This article provides an overview of the legal and organisational framework introduced in Myanmar for disaster risk management during the transition phase. In particular, it examines how and to what extent governance elements have been integrated into the system to meet local societal needs. The focus is on identifying challenges, gaps and opportunities in local governance structures. The study employs a mixed-methods analysis approach. This involved conducting 28 expert interviews with Yangon-based disaster management institution members as well as a quantitative household survey of 896 people in eight Yangon townships. Additionally, an in-depth analysis of government documents and reports was conducted. The study shows that the general framework for implementing governance aspects was already well established when the political system changed again in 2021. In practice, however, governance aspects remain challenging.

Disaster preparedness and resilience at household level in Yangon, Myanmar - Sophie-Bo Heinkel; Benni Thiebes; Zin Mar Than; Toe Aung; Tin Tin Kyi; Win Lei Mar; Saw Sandar Oo; Christian Miller; Marlene Willkomm; Win Maung; Zin Nwe Myint; Khin Khin Soe; et al. (Natural Hazards, 2022)
Resilience has become important in disaster preparedness and response. Unfortunately, little is known about resilience at the household level. This study presents the results of a survey into individual and household level preparedness to disaster events in Yangon, Myanmar, which is prone to natural disasters such as tropical cyclones, flooding, and earthquakes. The study aimed to understand societal resilience and to provide information that could be used to develop a holistic framework. In four different Yangon townships, 440 households were interviewed. The results of the survey indicate how risk preparedness could be improved by specific measures related to the following five factors: (1) increasing the general public’s knowledge of first aid and its role in preparedness; (2) improving mobile phone infrastructure and capacity building in its usage so that it can be used for communication during disasters, along with building up a redundant communication structure; (3) better use and organisation of volunteer potential; (4) more specific involvement of religious and public buildings for disaster response; and (5) developing specific measures for improving preparedness in urban areas, where the population often has reduced capacities for coping with food supply insufficiencies due to the high and immediate availability of food, shops and goods in regular times. The findings of this survey have led to specific recommendations for Yangon. The identified measures represent a first step in developing a more general framework. Future research could investigate the transferability of these measures to other areas and thus their suitability as a basis for a framework.

Population structure of Nga Myin Yinn Silonia silondia in the Ayeyarwady River, Myanmar, by mitochondrial DNA markers - Toe Toe Soe; Thida Lay Thwe; Pwint Thu Aye; Kyi Thar Myint; Than Than Lwin; Ye Win Thaung; Aye Aye Min; Shota Mitsui; Takeshi Terahara; Masato Endo; Masashi Yokota; M. Moshiur Rahman; et al. (Fisheries Science, 2021)

Assessing environmental impacts and change in Myanmar's mangrove ecosystem service value due to deforestation (2000–2014) - Ronald C. Estoque; Soe W. Myint; Chuyuan Wang; Asif Ishtiaque; Toe T. Aung; Lucy Emerton; Makoto Ooba; Yasuaki Hijioka; Myat S. Mon; Zhe Wang; Chao Fan (Global Change Biology, 2018)
Myanmar is one of the mangrove‐richest countries in the world, providing valuable ecosystem services to people. However, due to deforestation driven primarily by agricultural expansion, Myanmar's mangrove forest cover has declined dramatically over the past few decades, while what remains is still under pressure. To support management planning, accurate quantification of mangrove forest cover changes on a national scale is needed. In this study, we quantified Myanmar's mangrove forest cover changes between 2000 and 2014 using remotely sensed data, examined the environmental impacts of such changes, and estimated the changes in the economic values of mangrove ecosystem services in the country. Results indicate that Myanmar had a net mangrove loss of 191,122 ha over the study period. Since 2000, Myanmar has been losing mangrove forest cover at an alarming rate of 14,619 ha/year (2.2%/year). The loss was predominant in Rakhine and Ayeyarwady. The observed mangrove forest cover loss has resulted in decreased evapotranspiration, carbon stock, and tree cover percentage. Due to deforestation, Myanmar also suffered a net loss of 2,397 million US $/year in its mangrove ecosystem service value (i.e. 28.7% decrease from 2000), in which maintenance of fisheries nursery populations and habitat and coastal protection were among those services that were greatly affected. We suggest that intensive reforestation and mangrove protection programs be implemented immediately. Agroforestry and community forestry programs are encouraged in areas that are under immense pressure from paddy field expansion, fuelwood extraction, charcoal production, and fish and shrimp farming activities. Potential alternative sustainable solutions should include intensive government‐led private forest plantations or community‐owned forest plantations to be developed with care by local farmers, nongovernmental organizations, and business owners.